Necrotising fasciitis presenting as a blister: A case report on improving early recognition of surgical site infection following caesarean delivery - Alison Rothman; Nnabuike Chibuoke Ngene (Elsevier, 2024)
Early recognition and treatment of surgical site infection (SSI) may prevent devastating consequences of wound infections complicating caesarean delivery (CD). SSI complicates 3-15% of CDs; among the severe forms are necrotising fasciitis (NF) and clostridial gas gangrene, with the latter being the most rapidly spreading and fatal. The aim of this report is to improve early recognition of SSI complicating CD.An obese 32-year-old woman, gravida 2 para 1, with a previous uncomplicated vaginal delivery had a CD for fetal compromise in a district hospital. On day 6 after delivery, she presented to the same district hospital with a small blister located on her abdomen above the CD wound. The area around the blister was firm but had no crepitus. The blister was managed expectantly but spread rapidly and had a dusky colour. Both the blister and the surgical site for CD subsequently became foul smelling and the patient was managed in a regional hospital, where she had antibiotic therapy, wound debridement, negative-pressure wound therapy, and secondary wound closure. Healing was complete 69 days after the debridement. The histological report of the wound biopsy confirmed NF.In conclusion, blistering around a surgical site is suggestive of NF. Healthcare professionals managing surgical wounds should have ongoing training on SSI to prevent lack of problem recognition in wound care. All healthcare facilities managing surgical wounds should establish a functional wound care clinic to improve early recognition and treatment of SSI. This entails effective integration of postnatal and CD wound services to improve the care of SSI. Therefore, the algorithm included in this article will be invaluable to care providers.